PENGARUH KREATIVITAS DAN PENGGUNAAN MEDIA SOSIAL TERHADAP MINAT BERWIRAUSAHA MAHASISWA - Azka Nadya, Wuzira; Agrita, Tri Wera; Dwi Prasetyo, Oktavian; Fauziah, Fauziah; Muazza, Muazza (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
A country's potential can develop with a young generation interested in entrepreneurship and always supported by wise social media users. Finally, there are currently many young people who want to be developed in the region. So, it cannot be denied that the creative young generation will create ideas or concepts that are useful for developing more potential businesses. This research aims to explore the imaginative effects of the younger generation and the use of social media in generating interest in entrepreneurship. To detect the impact between several variables studied, the method used was an associative analysis approach, where the population was students from the Muhammadiyah University of Muara Bungo from the Faculty of Teacher Training and Education and the Faculty of Technology, Health and Science. The number of samples used in this research was 35 students. The sampling technique is purposive sampling, and a questionnaire is given to students who are the primary data source and measured using a Likert Scale. Then, the research instrument is tested for data quality and prerequisite tests to detect the impact of creativity and social media use on the younger generation's entrepreneurial interest. The SPSS application assists data processing. 25. The result is that creativity and the use of social media influence the development of the entrepreneurial interest of the younger generation.